Proximate Analysis of Selected Vegetables Sold in Yankaba Market Kano State, Nigeria - Ibrahim Mohammed , Musa; Mohammed Umar, Hauwa (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
This research examines the proximate contents of broccoli, cauliflower, curly kale, and red cabbage sold in Yankaba Market Kano State, Nigeria. Samples of these vegetables were procured from the market and analysed for proximate (moisture, protein, fat, ash, and fibre) contents. The proximate compositions were determined using the Association of Official Analytical Chemists (AOAC) method. The proximate analysis results reveal that the moisture content of the vegetable samples ranged from 11.73 to 82.52%, protein from 1.70 to 24.32%, fat from 0.25 to 1.09%, ash from 1.33 to 7.31%, dietary fibre from 2.11 to 17.30%, and carbohydrate from 9.83 to 38.56%. All the vegetables were low-fat and nutritious, but the levels of nutrients vary. The study discovered that the vegetables from the Yankaba market contained some appreciable amount of essential nutrients needed to maintain good nutritional status that will benefit consumers.